The Effect of Promotion and Destination Image on Interest in Revisiting Artificial Tourist Attractions (Case Study Theme Park Dunia Fantasi Ancol) - Nugraha, Rizki Nurul; Syah Putra, Eka (West Science Interdisciplinary Studies, 2024)
This study aims to: (a) to identify the effect of promotion on the interest in visiting Dunia Fantasi Theme Park (b) to identify the effect of destination image on the interest in visiting Dunia Fantasi Theme Park (c) to identify the extent to which promotion and destination image together affect the interest in visiting Dunia Fantasi Theme Park. This research applies an associative method with a quantitative approach. The research population includes tourists who have visited the Dunia Fantasi Theme Park. Sampling was done by simple random sampling with a sample size of 100 people. Data were collected through the use of questionnaires and processed with the IBM SPSS version 25 application. Data analysis in this study used multiple linear regression methods. The results of the study indicate that: (a) promotion has a positive impact on tourists' revisit interest in Dunia Fantasi Theme Park, which is supported by a regression coefficient of 0.309 and a significance of 0.000 <0.05. (b) destination image has a positive effect on tourists' revisit interest in Dunia Fantasi Theme Park, as evidenced by a regression coefficient of 0.460 and a significance of 0.000 <0.05. (c) promotion and destination image together have a positive impact on tourists' interest in revisiting at Dunia Fantasi Theme Park, as evidenced by the F value of 100,600 and a significance of 0.000 <0.05.